2010
DOI: 10.1387/ijdb.082735hc
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of thymosin beta4 promotes abnormal tooth development and stimulation of hair growth

Abstract: Thymosin β β β β β4 has multi-functional roles in cell physiology. It accelerates wound healing, hair growth and angiogenesis, and increases laminin-5 expression in corneal epithelium. Furthermore, thymosin β β β β β4 stimulates tumor growth and metastasis by induction of cell migration and vascular endothelial growth factor-mediated angiogenesis. Using a construct on the skinspecific keratin-5 promoter, we have developed thymosin β β β β β4 over-expressing transgenic mice to further study its functional roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…In addition, gene expression of DSPP, BSP, OCN, ON, and collagen type I related to mineralization is significantly decreased when Tβ4 is inhibited in the odontoblast-like cells MDPC-23 by Tβ4 siRNA [13]. Moreover, we recently reported that Tβ4-overexpressing transgenic mice promote abnormal hair growth and tooth development as observed by abnormally shaped white teeth and dull incisors [14]. Although Tβ4 peptide accelerates bone regeneration and osteogenesis of tooth extraction sockets [15], the underlying molecular mechanisms for controlling odontoblastic growth and differentiation by Tβ4 are still not fully understood in regenerative dentistry.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, gene expression of DSPP, BSP, OCN, ON, and collagen type I related to mineralization is significantly decreased when Tβ4 is inhibited in the odontoblast-like cells MDPC-23 by Tβ4 siRNA [13]. Moreover, we recently reported that Tβ4-overexpressing transgenic mice promote abnormal hair growth and tooth development as observed by abnormally shaped white teeth and dull incisors [14]. Although Tβ4 peptide accelerates bone regeneration and osteogenesis of tooth extraction sockets [15], the underlying molecular mechanisms for controlling odontoblastic growth and differentiation by Tβ4 are still not fully understood in regenerative dentistry.…”
Section: Introductionmentioning
confidence: 97%
“…Tβ4 mediates differentiation of endothelial cells (Malinda et al, 1997), keratinocytes (Philp et al, 2004b), and oligodendrocytes (Santra et al, 2012). We previously reported that Tβ4-overexpressing transgenic mice have abnormal tooth development and enhanced stimulation of hair growth (Cha et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research demonstrates the powerful effect of Tb4 on ageing skin, in part because of its ability to stimulate the production of collagen and elastin [71]. Moreover, the well-documented ability of Tb4 to enhance hair growth stay in line with the reported properties of AcSDKP [72,73].…”
Section: Discussionmentioning
confidence: 88%